Optimization of the Preparation Process of 6'-O-Caffeoylarbutin Liposomes and Its Activity - Mengzhe LIU; Kangjia HAN; Wenbo WANG; Yang YANG; Sida XIE; Ping ZHAO; Junming XU; Yuanping HE; Xiaoqin YANG (Shipin gongye ke-ji)
Objective: To optimize the preparation process of 6'-O-caffeoylarbutin liposomes using the Box-Behnken response surface methodology, and to characterize their structure and evaluate their activity. Methods: The ethanol injection method was used. Initially, single-factor experiments were conducted to investigate the effects of the mass ratio of soybean lecithin to cholesterol, the pH of phosphate-buffered saline (PBS), the amount of 6'-O-caffeoylarbutin, stirring temperature, and stirring time on the encapsulation efficiency of 6'-O-caffeoylarbutin liposomes. Based on the results of single-factor experiments, the Box-Behnken response surface methodology was employed to optimize the preparation process. The liposomes were then characterized in terms of microscopic morphology, particle size, in vitro antioxidant activity, and in vitro tyrosinase inhibition activity. Results: The optimal conditions for preparing liposomes were found to be a soybean lecithin to cholesterol mass ratio of 7.10 (g/g), a PBS pH of 6.90, an amount of 820 μL of 6'-O-caffeoylarbutin, and stirring at 45 ℃ for 30 minutes, resulting in a maximum encapsulation efficiency of 80.93%±0.82%. The obtained liposomes exhibited a vesicular structure, with a nearly spherical morphology. The particle size ranged primarily from 78 to 200 nm, with an average size of 127.42±0.76 nm and a polydispersity index of 0.259±0.006. The Zeta potential mainly ranged from −80 and −40 mV. The IC50 values for 6'-O-caffeoylarbutin and its liposomes in scavenging DPPH radicals were 0.27±0.04 and 0.26±0.03 mg/mL, respectively. For ABTS+ radicals, the IC50 values were 0.13±0.02 mg/mL and 0.17±0.03 mg/mL, and for OH radicals, the IC50 values were 0.10±0.03 and 0.17±0.02 mg/mL. The total reducing power for iron ions was significantly higher for 6'-O-caffeoylarbutin than for its liposomes. The maximum inhibition rates of the liposomes against tyrosinase monophenolase activity were 48.81%±0.51% and 42.56%±1.25%, with IC50 values for diphenolase inhibition of 0.14±0.02 and 0.16±0.03 mg/mL, respectively. Conclusion: The liposomes prepared under the experimental conditions exhibited high encapsulation efficiency and small particle size for 6'-O-caffeoylarbutin, demonstrating good in vitro antioxidant activity and tyrosinase inhibition. This study provides a reference for the deep development and utilization of 6'-O-caffeoylarbutin.